Agronomic performance and biochemical attributes of yellow-pulped elite sweet cassava clones - Fuhrmann, Elisiane; Vieira, Eduardo Alano; Fialho, Josefino de Freitas; Faleiro, Fabio Gelape; Carvalho, Luiz Joaquim Castelo Branco de (Científica, 2019)
Cassava storage root is the staple food of most of the Brazilian population. In this study, 13 cassava clones were evaluated for agronomic and biochemical traits compared to the control variety IAC 576-70. The experiments were conducted at Embrapa Cerrados during two harvest seasons. A randomized complete block design was used with three replicates, each plot consisting of 4 rows of 10 plants. Trait means were grouped by the Scott-Knott clustering test at 5% probability. The results highlighted clones 273/08 and 259/08, based on first branch height; 90/08, 272/08, 273/08, 497/08, 259/08, and 450/08, based on plant height; 94/08 and 272/08, based on shoot weight without the original stem cutting; 26/08, 272/08, 259/08, and 450/08, based on root starch percentage; and 215/08, based on root yield. In the 2011/2012 season, all clones showed cooking time less than 30 minutes. Regarding root protein content, clones 26/08, 90/08, and 91/08 were highlighted. HCN levels in cassava roots were below 100 mg kg-1 in all clones evaluated. We found elite clones with high levels of root carotenoids, especially clones 91/08, 94/08, 215/08, 246/08, 272/08, and 497/08. These clones have great potential for direct use by producers, and can be used as promising parents in genetic breeding programs of cassava.